ATTITUDES AND BEHAVIORS TOWARD DENTAL HEALTH PRACTICES - M. Mohseni; Sh. Hedayat (Tehran University of Medical Sciences, 1977)
The present study examines the hypothesis that the attitudes and behaviors of people toward dental health practice varies with such factors as locality (urban- rural) age and levels of education. For this study 1085 urban and 871 rural heads of households have been interviewed. The results indicated that locality and age influences the behaviors of the respondents but the general attitude leads no relationship to the locality.